Cloning, characterization and expression analysis of caspase-8 genes from the golden pompano (Trachinotus ovatus) - Fan Da; Xiaoju Wan; Guixiang Lin; Jichang Jian; Jichang Jian; Shuanghu Cai; Shuanghu Cai (Frontiers in Marine Science, 2022)
Bacterial infection triggers apoptosis and immunity by regulating the expression of caspases. In this article, we report two caspase-8 paralogs, termed ToCas8 and ToCas8-like, from an economically important teleost golden pompano (Trachinotus ovatus). Caspase-8 is a classic cysteine protease that is essential for the initiation and execution of apoptosis and is a critical regulator in initiating death receptor-induced programmed cell death. The two proteins encoded by ToCas8 and ToCas8-like were characterized by multiple sequence alignment and protein structure analysis showing similarity to their counterparts in vertebrates and exhibiting typical features of the Caspase-8 protein family. Gene synteny analysis further confirmed that two isoforms of caspase-8 genes exactly existed in golden pompano. Phylogenetic analysis showed that the Caspase-8 proteins of the selected species in the study were clustered together, and Cas8 and Cas8-like were clustered into two different subgroups. In addition, ToCas8 and ToCas8-like were widely distributed and both were expressed at high levels in gill, kidney and intestinal tissues. Transcript levels of ToCas8 and ToCas8-like were significantly upregulated in response to LPS and Poly(I:C) challenges, suggesting that caspase-8 genes are involved in the immune response to pathogens. In summary, we have identified two isoforms of caspase-8 in golden pompano that are involved in the immune response. These findings will expand our understanding of the evolutionary history and functional characteristics of caspase-8 genes in vertebrates.